The Implementation Effort Islamic Law Norms in Activities for Overcoming Pornography and Pornoaction on Mass Media - Ramlani Lina Sinaulan (International Journal of Nusantara Islam, 2017)
This paper discusses the effort Islamic Law norms in activities for overcoming pornography and porno-action on mass media. By using normative legal research, the result found that the concept of Islamic law, behave based on sharia, shows the importance of shaping the personality traits of Islam (syakhsiyya Islāmiyya) and based on the devotion and faith. Because of the relation to the formulation of the rule of law against pornography behavior, it can not be designed, prepared and formulated based on social values. Based on the facts of society, as a result of the moral decadence that led to a permissive attitude towards their cultural infiltration, the social values in assessing the behavior may become more permissive toward behavior. However, the use of religious norms which have universal properties will not change, and even capable of elastic with the times.